2019
DOI: 10.1002/brb3.1206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of sequential bilateral low‐frequency rTMS over dorsolateral prefrontal cortex on serum level of BDNF and GABA in patients with primary insomnia

Abstract: Objective This study aimed to investigate the effect of sequential bilateral low‐frequency repetitive transcranial magnetic stimulation (rTMS) over dorsolateral prefrontal cortex (DLPFC) on patients with primary insomnia (PI). Methods A total of 32 eligible right‐handed participants diagnosed by PI according to International classification of sleep disorders (ICD‐3) were recruited into this study. Participants received 10 daily sessions of sequential bilateral 1 Hz rTMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…In one study of patients with primary insomnia (Feng et al 2019), γ-aminobutyric acid (GABA) neurotransmitter levels and brain-derived neurotrophic factor (BDNF) levels in blood serum were measured as objective indicators of sleep with higher levels associated to better sleep regulation (Datta et al 2015;Gottesman 2002). Motorevoked potentials (MEP) were also measured to reflect cortical excitability.…”
Section: Biological Measurement Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study of patients with primary insomnia (Feng et al 2019), γ-aminobutyric acid (GABA) neurotransmitter levels and brain-derived neurotrophic factor (BDNF) levels in blood serum were measured as objective indicators of sleep with higher levels associated to better sleep regulation (Datta et al 2015;Gottesman 2002). Motorevoked potentials (MEP) were also measured to reflect cortical excitability.…”
Section: Biological Measurement Outcomesmentioning
confidence: 99%
“…rTMS can be used as a mapping tool to study neuronal networks for pre-surgical planning, diagnostic purposes (Valero-cabré et al 2017), and to examine brain cortex functionalities (Valero-cabré et al 2017;Nardone et al 2013). In addition, it has recently been explored in neurology and psychiatry communities to determine its therapeutic potential for different sleep pathologies such as insomnia (Feng et al 2019), sleep bruxism (Zhou et al 2016), and restless legs syndrome (Lin et al 2015). To date, the exact mechanism by which rTMS is thought to influence sleep has yet to be fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] Hence, aim to improve subjects compliance and achieve acupoint effect, we choose rMS at HT7 acupoint in the experimental group in a high-quality randomized controlled trial. Although studies have showed the efficacy of rTMS for CI, [ 32 , 33 ] it is still lack rMS at acupoint randomized controlled trial, as well as the relevant mechanism research.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies within the medical literature attest to a correlation between the activity of parvalbumin cells, gamma oscillations, and social deficits. Modulation of gamma oscillations, especially over the dorsolateral prefrontal cortex DLPFC), has been associated with improvements in cognitive performance …”
Section: Introductionmentioning
confidence: 99%